FAUNA IKAN AIR TAWAR DI PERAIRAN KAWASAN GUNUNG SAWAL, JAWA BARAT, INDONESIA [The Freshwater Fish Fauna of Sawal Mountain Region, West Java, Indonesia] - Haryono, Haryono (Research Center for Biology-Indonesian Institute of Sciences, 2017)
This study aimed to assess fish diversity and its related aspects in the Sawal Mountain Region, the watershed Citanduy in Ciamis, West Java, Indonesia. The study was conducted by grouping into four zones based on forest condition and the order of the river. The fisheswere sampled by using elektrofishing. This study recorded 12 species which Barbodes binotatus is the most abundant and widely local distributed, i.e. 20.09 individu/station and occupied 78.60 % of the area. Based on species status, as much as 75% species have wide geography distribution (common species) and the rest was introduced species. As much as 50% (6 species) have the potency as consumption fish, 25% (3 species) as ornamental fish, 17% (2 species) both as ornamental and consumption, and 8% (1 species) is stil unknown for the benefit.